Pengaruh Variabel Keuangan dan Regulasi terhadap Harga Saham Perbankan di Indonesia: Studi Kasus pada Perbankan Indonesia - Tenika, Eiyagina; Muchtar, Susy (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
One user of financial reporting information is investors. An investor's main interest in a company's financial statements is to find out how profitable the company is from the perspective of capital investment in the company. One way to get more accurate information is to carry out financial ratio analysis. The data analysis used in this research is descriptive analysis and multiple regression analysis. This calculation uses statistical methods supported by the SPSS for Windows program to measure the impact of a bank's financial performance on its share price. 61.00% of the variation in all independent variables (CAR, RORA, NPM, ROA, and LDR) can explain the dependent variable (share price). The remaining 39.00% is explained by other variables not proposed in this research.